Revisiting the Concept of Othering: A Structural Analysis. (October 2021) - Jacob, Jean Daniel; Gagnon, Marilou; Perron, Amélie; Canales, Mary K.
Abstract : The various ways in which nurses relate and interact with patients, who are considered marginal, vulnerable, and in some ways "different, " tend to revolve around the concept of othering. To date, much attention has been given to the immediate situation in which othering may take place, both in terms of process (occurring within interactions) and outcomes (exclusion and marginalization). Drawing on current literature from feminist studies and critical theory, we have drawn attention to broader historical, political, cultural, and social factors that come to shape nurse-patient relationships and propose a new dimension to the concept: structural othering.